PAS steps to achieve alignment - Arkesteijn, Monique (A+BE | Architecture and the Built Environment, 2019)
The focus in this chapter is on the component steps of PAS (see Figure 5.1 and Figure 5.2). CRE alignment is achieved, as has been shown in chapter 4, if stakeholders can use PAS successfully. PAS is successful if the stakeholders are able to perform each step of PAS. I assume that the stakeholders can perform steps 1 (specifying decision variables), 3 (assigning weights) and 4 (determining design constraints) because these type of steps are part of other multi criteria decision analysis as well. However, it is not known if stakeholders are able to perform the new step 2 (determining preferences) and step 5a (design alternatives) and are willing to select the alternative with the highest overall preference score in step 6. Preferably, this new alternative has a higher overall preference score than the overall preference score in the current situation. However, if the boundary conditions are strict this is not always possible. PAS has been tested in three pilots. This chapter has the following structure: –– TU Delft pilot for the food facilities in paragraph 5.1; –– TU Delft pilot for lecture halls in paragraph 5.2; –– Oracle’s pilot for office locations in paragraph 5.3; –– Pilot study comparison and conclusion in paragraph 5.4.